Mathematical Aspect of Optimal Control Finite Element Method for Navier-Stokes Problems (Journal of Computational Mathematics, 1984)
This study deals with the theoretical basis of optimal control methods in primitive variable formulation and penalty function formulations of Navier-Stokes problems. Numerical examples demonstrating application are provided.